Functional Connectivity Analysis and Detection of Mental Fatigue Induced by Different Tasks Using Functional Near-Infrared Spectroscopy - Peng, Yaoxing; Li, Chunguang; Chen, Qu; Zhu, Yufei; Sun, Lining (Frontiers in Neuroscience, 2022)
Abstract Objectives: The objective of this study was to investigate common functional near-infrared spectroscopy (fNIRS) features of mental fatigue induced by different tasks. In addition to distinguishing fatigue from non-fatigue state, the early signs of fatigue were also studied so as to give an early warning of fatigue. Method: fNIRS data from 36 participants were used to investigate common character of functional connectivity network corresponding to mental fatigue, which was induced by psychomotor vigilance test (PVT), cognitive work or simulated driving. To analyze the network reorganizations quantitatively, clustering coefficient, characteristic path length and small-worldness were calculated in five sub-bands (0.6-2.0Hz, 0.145-0.600Hz, 0.052-0.145Hz, 0.021-0.052Hz and 0.005-0.021Hz). Moreover, we applied a Random Forest method to classify three fatigue states. Results: In a moderate fatigue state: the functional connectivity strength between brain regions increased overall in 0.021-0.052Hz, and an asymmetrical pattern of connectivity (right hemisphere > left hemisphere) was presented. In 0.052-0.145Hz, the connectivity strength decreased overall, the clustering coefficient decreased, and the characteristic path length increased significantly. In severe fatigue state: in 0.021-0.052Hz, the brain network began to deviate from small-world pattern. The classification accuracy of fatigue and non-fatigue was 85.4%. The classification accuracy of moderate fatigue and severe fatigue was 82.8%. Conclusion: The preliminary research demonstrates the feasibility of detecting mental fatigue induced by different tasks, by applying the functional network features of cerebral hemoglobin signal. This universal and robust method has the potential to detect early signs of mental fatigue and prevent relative human error in various working environments. Keywords: mental fatigue detection, functional near-infrared spectroscopy, functional network characteristics, common signs of fatigue tasks